Improved photoresponse performances of V2O5 and rGO. Issue 7 (3rd July 2019) - Wu, Jie; Ding, Simin; Huang, Zongyu; Li, Hongxing; Huang, Kai; Qi, Xiang; Li, Jun
Abstract: The vanadium pentoxide nanowires (V2 O5, several microns) have been manufactured via solution method for photodetectors. For further to improve the photoelectric performance, a hybrid nanostructure of V2 O5 /graphene oxide (GO) and V2 O5 /reduced graphene oxide (rGO) was adopted. Besides that, the photoelectric performance of (V2 O5, V2 O5 /GO, V2 O5 /rGO) were measured, they were made into a form of composite paper with a wavelength of 532 nm laser irradiation, as the incident light power increases at room temperature, the photocurrent increases, especially V2 O5 /rGO (50 μA, 10 mA), which is 10 times as much as V2 O5 (4.12 μA, 13 mA), and 5 times as much as V2 O5 /GO (9.8 μA, 10 mA). It's ascribed to the dispersion of rGO (GO) layer between the build-up of V2 O5, improving the build-up between them, and the excellent electrical conductivity of rGO layer can rapidly move the photo-generated carriers, thereby greatly increasing the photocurrent density. These results pave an effective approach to further improve the practical application of V2 O5 in photodetection.